Analysis of Artificial Intelligence Design Incorporated into Design of Street Space in Small Cities - Lei Song (EAI Endorsed Transactions on Energy Web, 2023)
INTRODUCTION: At present, China's urbanization continues to develop, but the level of urban planning and design has not kept pace with the progress of development, especially the creation of street space in small cities, which is still not able to adapt to the current needs of people's cultural life. With the development of the economy and science and technology, artificial intelligence and other information technologies are constantly integrated into daily life. Therefore, utilizing artificial intelligence for street space design research is significant.